Frontiers in the Roman world : proceedings of the ninth Workshop of the International Network Impact of Empire (Durham, 16-19 April 2009) - Impact of Empire (Organization) (2011)
This volume presents the proceedings of the ninth workshop of the international network ‘Impact of Empire’, which concentrates on the history of the Roman Empire and brings together ancient historians, archaeologists, classicists and specialists on Roman law from some thirty European, North American and Australian universities. This volume focuses on different ways in which the Roman Empire created, changed and influenced (perceptions of) frontiers. The volume is divided into five larger sections: the meaning of 'frontiers', consequences of frontiers, religious frontiers, shifting frontiers and crossing 'frontiers'. In this way, the volume pays attention to different kind of ‘frontiers’ within the Roman Empire, and to their importance for the functioning of the Roman Empire over a longer period of time.